Hubungan tweed triangle dan posisi bibir terhadap garis estetik (Relationship between tweed triangle and the lips position to esthetic line) - Intan Oktaviona; I.G.A. Wahju Ardani; Achmad Sjafei (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: The aimed of almost all of patient came for orthodontics treatment, were to recover face esthetic or their profile. The facial profile not only determined by the hard tissue, but will also be influenced by the soft tissue such as nose, lip, and chin. Tweed has done face analysis with cephalometric by using three angles which are FMA, FMIA, and IMPA. There are many facial profile analysis that usually use in lateral cephalometric one of them is Ricketts analysis that draw the line from pogonion to the tip of nose. The biggest tribe in Indonesia is Javanese, the Javanese have a specific characteristic. Javanese people do not have a long nose and the chin not really uppermost, thick lip, convex profile and female’s profile more convex than male. Purpose: The study was aimed to examine the relation between Tweed triangle, upper lip and lower lip to esthetic line according to Ricketts. Methods: The facial profile pictures of subjects which were taken base on sample criteria changed into silhouette black and white. The photo selected by orthodontist and lay persons. Then the lateral cephalometric radiograph was taken and measured the angle of Tweed triangle and the lip position to esthetic line. Results: The FMA were 28.830, FMIA were 56.740 and IMPA were 94.430. The upper lip distance among males were closer to the esthetic line than female. The lower lip of males located in front of esthetic line and female lower lip located rare of esthetic line. Conclusion: There was corelation between FMA and FMIA with lower lip. There was no corelation between IMPA towards upper lip and also lower lip.Latar belakang: Tujuan dari hampir seluruh pasien yang datang untuk perawatan ortodonti adalah untuk memperbaiki estetis wajah atau profilnya. Profil fasial tidak hanya ditentukan oleh jaringan keras, akan tetapi juga akan sangat dipengaruhi oleh jaringan lunak hidung, bibir, dan dagu. Tweed melakukan analisis wajah pada sefalometri menggunakan 3 sudut dalam segitiga yaitu FMA, FMIA, dan IMPA. Beberapa analisis profil facial yang sering digunakan pada sefalometri lateral antara lain analisis Ricketts yang merupakan garis yang ditarik dari pogonion ke ujung hidung. Suku terbesar di Indonesia adalah suku Jawa, suku Jawa memiliki ciri ragawi tertentu antara lain: hidung orang Jawa tidak terlalu mancung dan dagu tidak begitu menonjol, bibir tebal, proporsi jaringan lunak yang cembung dan perempuan lebih cembung daripada laki–laki. Tujuan: Meneliti hubungan antara tweed triangle terhadap posisi bibir atas dan bibir bawah terhadap garis estetik. Metode: Foto profil wajah berdasarkan kriteria sampel, yang dibuat siluet hitam putih, dan selanjutnya dipilih oleh dokter gigi spesialis ortodonti dan orang awam. Selanjutnya sampel terpilih akan difoto sefalometri lateral dan akan dihitung besarnya sudut Tweed triangle dan posisi bibir terhadap garis estetik. Hasil: Besarnya nilai FMA 28.830, FMIA 56.740, dan IMPA 94.430. Jarak bibir atas laki-laki lebih mendekati garis estetik dibandingkan dengan perempuan, sedangkan bibir bawah laki – laki terletak di depan garis estetik dan bibir bawah perempuan mendekati garis estetik. Simpulan: Terdapat hubungan antara FMA dan FMIA terhadap bibir bawah. Tidak terdapat hubungan antara IMPA terhadap bibir atas maupun bibir bawah.